Territorial Assessment of the Urban Peripheries Fragmentation in Fez, Morocco - El Bouaaichi, Amina (ARCC Conference Repository, 2013)
The paper discusses the problematic of the urban fragmentation at the level of the peripheriesof Fez, Morocco. The paper aims at dealing with complex urban issues namely: How can we nowadays assess territorially the scales of the urban in this large city, based on the observation of the urban peripheries fragmentation, which are so sensitive and strategic, with a plural and complex reality, interactiveand in full motion? On what basis and according to which criteria can we define the degrees of this fragmentation quite visible spatially from its peripheral extensions?There are two main objectives in this study. First, we shall demonstrate if this spatial fragmentation regenerates any social fragmentation. In this sense, we have to master the indicators allowing us to evaluate the presence of this fragmentation. This approach allowed us to manage its meaning in terms of urban integration and/or exclusion. Second, we shall identify the diversity of peripheral scales according to how the inhabitants themselves visualise their territories. At the level of methodology, we adopt two complementary qualitative approaches based on an extensive and long fieldwork. The "renewed" typological approach adopted in the first part has been completed in the second-level by the "axiological" approach, essentially qualitative. The analysis of the issue refutes clearly any correlation between mechanical spatial fragmentation and social fragmentation. It follows from the in-depth analysis that the "non-regulatory city» is not at all "another city", it has similarities and articulations with the conventional city. On the other hand, our research confirms the importance and size of these different forms of adherence, symbolic and real, to the urban, through the individual and collective access to products and services of the "Urban," tangible or intangible. These results call for a critical examination of the fragmentation connotations as a shared and irreversible processat the core, related to an advanced and desirable urbanization.